Age-defying fitness: How can combining resistance and aerobic exercise help elderly adults increase muscle strength? - Gunawan, Gunawan; Saparia, Andi (UIR Press, 2023)
The population of elderly individuals in the village of Tinggede, Indonesia, continues to increase. It is crucial for the ageing population to maintain good fitness throughout the ageing process. Ageing in the elderly encompasses a range of issues, from declining motor function to muscle strength loss. Therefore, it is important for the elderly to preserve muscle strength through physical exercise to ensure independent functioning. This research aimed to investigate the effects of a combination of resistance and aerobic exercises on muscle strength in healthy elderly individuals. The study involved a sample of 30 male elderly individuals aged 60 years and older. The treatment group was given a combination of resistance exercise and aerobic exercise, while the control group was given aerobic exercise. Resistance exercise is given three times per week with a progressive increase in sets and reps. While aerobic exercise is given seven times per week for 40 minutes per session. Participants were examined for muscle strength before and after the intervention using a digital hand grip dynamometer (DHD). The analysis performed included paired t-test and independent t-test with p <0.05. The results demonstrated a significant increase in hand grip strength among the participants who underwent the exercise programme compared to the control group. These findings suggest that a progressive increase in sets and repetitions for each exercise activity can effectively enhance muscle strength in the elderly. However, it is pivotal to note that this study was limited to a single village. Nonetheless, the exercise combination proposed in this study provides valuable insights for sports medicine research and can be utilised as a reference for designing exercise programmes targeting healthy elderly individuals.